Performance of an automatic temperature and salinity control system for fish rearing - Makhtar, Nur Lailina (2014)
Water temperature and salinity has significant effect in fish growth. Inappropriate temperature and salinity in the fish tank can develop disease for the fish and influence the profit gained by the fish farmers. It is important to develop a system that is able to control and monitor temperature and salinity in a fish tank. However, fish farmers prefer to use manual method. This is because manual method is easy and is available at lower cost. But by using man power, there is some limitation that appears like the data taken is not accurate and the data is not collected at the same time during the experiment. The objective of this research was to develop an automatic control system for temperature and salinity in the fish tank. Arduino Uno control board that is equipped with Atmega328 microcontroller is used to control and monitor temperature and salinity inside the fish tank. WZP-191 temperature sensor and Vernier salinity sensor is connected to the control board to measure temperature and salinity. The developed system was tested at FRI Pulau Sayak, Kota Kuala Muda, Kedah for 4 consecutive weeks to see the performance of the developed system. Besides that, the effect of temperature (at 25OC and room temperature) and salinity (at 25 ppt and 30 ppt) on the Lates calcarifer’s growth was also studied. Total of 150 L. calcarifer’s juveniles were used in this experiment. All the fishes were weighted and the lengths were measured every week to see the effect of different temperature and salinity combination to the fish. Data were analyzed by SPSS to determine the best temperature and salinity to grow L. calcarifer in tanks. Compared with another temperature and salinity combination in this study, result showed that Treatment 1 tanks (Temperature: 25OC, Salinity: 25 ppt) was suitable to rear juvenile L.calcarifer as weight gain, SGR and PER were showing significant differences in the 2-way ANOVA test conducted. The mean weight gain ± standard error for the weight gain, SGR and PER for Treatment 1 tanks are as follows 17.02 ± 1.08 g, 2.25 ± 0.22 and 1.49 ± 0.14 correspondingly. It can be concluded that the developed system was able to control and monitor temperature and salinity in a fish tank. It is suggested that the fish farmers use the developed system in their fish tank to gain more profit.